Cameroon : Request for a Three-Year Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Cameroon. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses Cameroon's Request for a Three-Year Arrangement Under the Extended Credit Facility (ECF). Cameroon has been hit by significant export price declines and security threats since 2014. Oil revenue declined and security and humanitarian spending increased, while large infrastructure programs continued, leading to widening fiscal and current account deficits, rapidly accumulating external debt and a decline in imputed reserves. The Cameroonian authorities are requesting a three-year program under the ECF in the amount of SDR 483 million to restore external and fiscal sustainability, and lay the foundations for sustainable, private-sector led growth. The IMF staff supports the authorities' request for an ECF-supported program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet